Pengaruh Media Interaktif Educaplay pada Pembelajaran Matematika di Kelas III SD - Aisyah Falah Agdiyah; Syukriyah Mustopa; Kowiyah Kowiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the impact of using Educaplay interactive media on improving mathematics learning outcomes for grade III students. Based on a comparison of the results before and after the test, Educaplay was proven to increase student learning completion levels from 60% to 86.67%. Apart from that, Educaplay increases student motivation and involvement in the learning process so that it is more interactive and interesting. Educaplay provides a more diverse learning experience and helps students gain a deeper understanding of mathematics content.These results show that the use of technology-based media in learning has a positive impact on student achievement and participation and improves the quality of mathematics learning at the elementary school level.These results recommend the use of Educaplay as a learning medium to encourage active student participation and improve learning outcomes.